Seeking Validation Through Virtual Gifts: A Quranic Perspective On TikTok Live's Bizarre Trends - Attarwiyah, Nadiatul Maziyyah (ISTIFHAM, 2025)
This study examines the phenomenon of virtual gifts on TikTok Live as a new face of digital culture that has become increasingly performative, where social recognition is no longer built through authentic interaction but through commodified digital symbols. The research employs a qualitative tafsir-based approach, analyzing Qur'anic verses related to the ethics of social interaction and the realities of contemporary digital culture. The findings reveal that the mechanism of virtual gifts creates an ecosystem of attention and emotional capitalization, driving creators to display themselves—even through extreme acts—in pursuit of superficial social legitimacy. This pattern exposes a paradox: while creativity is facilitated, human dignity is simultaneously diminished, as the illusion of algorithmic recognition measures self-worth. From the Qur'anic perspective, this phenomenon is critiqued as a modern form of riya', as emphasized in QS. Al-Isra' [17]:70 on the innate dignity of humanity, QS. Al-Baqarah [2]:264 on the futility of deeds tainted by riya', QS. al-Hujurat [49]:11–13 on piety as the proper standard of social honor, and QS. al-Munafiqun [63]:4 on the danger of hollow self-image. In conclusion, the culture of pseudo-validation through virtual gifts must be repositioned—not as a space for riya' and instant recognition, but as a digital sphere that affirms spiritual identity, preserves dignity, and cultivates authentic values grounded in faith.